Do carcere à rua: um estudo sobre homens que saem da prisão - Carvalho Filho, Milton Júlio de (2006)
This ethnographic study describes and aims at interpreting the processes of recovering freedom by men who have lived the experience of criminal imprisonment in Brazil. It starts from the premise that imprisonment sets off values, traumas, behaviors and attitudes that are present when these subjects resume their lives after being released from prison. Freedom is not limited only to the opening of gates so that the subjects can leave the objective reality of having experienced imprisonment. The conception that persists about the ex-prisoners is that they are dangerous and devilish men, who are capable of catalyzing fear, insecurity and mistrust. They are considered the reverse side of civility, since they are dangerous, superfluous and susceptible of being exterminated. This image is also strengthened by the imprisonment heritage of being confined, by the vigilance and control perceived in the codes of ethics and conducts and the feeling of being strange that they feel when leaving the prison. To find out whether or not and to which extent imprisonment has been fixed on these subjects demanded a process of work, whose basic premise was a long life experience with this other. The basis was the narratives of fifty-two men, former prisoners who were interviewed and followed up for three years. The interpretation of these narratives enabled the acknowledgment not only of their creative and active potentials, but also the identification of several factors that resulted in the immobilization of their actions, plans and projects. Our starting point was to find out when the ex-prisoner ceases being considered an ex-prisoner? By giving voice to these subjects, we could understand the consequences of imprisonment in the attempts of being adapted to the outside world and/or of rebuilding their lives after prison. Based on their expressions, the prison itself was evaluated as a system and as such, the disciplinary techniques that were used were also evaluated. Michel Foucault and Irving Goffman s theoretical references were used to analyze the aspects of the imprisonment regime present in the ones that were subject to imprisonment and to analyze the consequences of this past of prison in the reconstruction of the identity of these subjects when they leave it. This past that is present in their lives was analyzed, and from it was confirmed that despite the drastic consequences of confinement, the subjects can react to them, with the aim of overcoming them to reach the emancipation status of a former prisoner, by thinking and acting free from imprisonment. The narratives were classified according to criteria of individual and group memory, analyzing their resignifications based on Michael Pollak. Conceptual schedules that were organized into chapters in this work stemmed from the analysis of the narratives: the singularities perceived in the research field that characterize the subjects, the exit from the prison and their introduction into the family and social milieu; their behaviors after prison, the re-signification of the delict and of the prison and finally the attempts of emancipation through work. From these schedules, it was possible to discuss issues referring to emancipation and identity, which were impacted by confinement, in terms of making their actions capable of overcoming the ex-prisoner status